Keterlambatan Penyediaan Rekam Medis Pasien Rawat Jalan di RSUD Kabupaten Bima Provinsi Nusa Tenggara Barat - Dinda Darmawati; Gamasiano Alfiansyah; Novita Nuraini; Selvia Juwita Swari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
The time of providing medical record documents to the polyclinic is one of the indicators in measuring patient satisfaction. The results of the preliminary study showed that 12 of the 13 observed medical record documents experienced delays in providing medical record documents. This is not in accordance with service standards, the minimum time for providing outpatient medical records is less or equal to 10 minutes. The purpose of the study was to analyze the factors causing the delay in providing medical record documents for outpatients at Bima Hospital. This research was a qualitative research, the research subject consisted of 5 informants. Collecting data through interviews and observations. Data were analyzed by content analysis. The results showed that the predisposing factor was that some officers did not attend training and did not know the standard time for providing outpatient medical records. Enabling factors were caused by the distance from the medical record room to the poly that is quite far, the lack of infrastructure such as the availability of shelves is still lacking, the use of tracers has not been maximized, and there are no trolleys. The reinforcing factor is caused by the unavailability of standard operating procedures for the provision of medical records. This study suggests hospitals to provide training to officers, socialize standard operating procedures for returning and providing medical records, adding trolleys as a means of distributing medical records, and using tracers to reduce missfiles.Keywords: medical record; delay; provision